SDS-Page Seed Storage Protein Profiles in Chili Peppers (Capsicum L.) - Owk ANIEL KUMAR; Sape SUBBA TATA (Notulae Scientia Biologicae, 2010)
Seed protein banding patterns (SDS-PAGE) were studied from eighteen genotypes of chili pepper (Capsicum L). A total of 21 protein polypeptide bands with molecular weight ranging from 18.6 to 72.0 kD were recorded. Among the genotypes CA18, CA21 and CA27 represented maximum number of protein bands (12). Band no. (11) and (5,12) are exclusive to C. annuum L. and C. frutescens L. genotypes respectively. Average percent similarity was highest (100%) between CA2 and CA8 genotypes and the UPGMA dendrogram represented low genetic diversity. The study revealed that considerable intra and inter-specific differences were found in the genotypes. The variability of protein profiles in the genotypes suggested that these selected genotypes can be a good source for crop improvement through hybridization programs.